Potential FSH-mediated molecular pathway to regulate follicle development in striped hamsters (Cricetulus barabensis) supported by strong correlative evidence - Huiliang Xue; Yunjiao Zheng; Chao Fan; Jinhui Xu; Lei Chen; Ming Wu; Laixiang Xu (PLoS ONE, 2025)
Scientific background Rational control of rodent populations is crucial for maintaining ecosystem balance and mitigating agricultural economic losses. Follicle development plays a pivotal role in determining animal population abundance, and photoperiod serves as the primary environmental cue affecting this process. Investigating the mechanisms through which photoperiod influences follicle development in the striped hamster ( Cricetulus barabensis ) offers a promising molecular target for the effective and sustainable management of rodent populations. Methodology This study employed hematoxylin and eosin (HE) staining to evaluate ovarian developmental status under different photoperiods, including quantification of follicles at various developmental stages and the number and thickness of granulosa cell layer, thereby elucidating the effects of photoperiod on follicle development. Subsequently, enzyme-linked immunosorbent assay (ELISA) was used to measure serum FSH and fecal E2 concentrations, while real-time quantitative PCR was performed to determine mRNA levels of CCND1 and CCND2 . Correlation analyses between these markers and follicle counts were conducted to identify key factors involved in follicle development. Furthermore, both real-time quantitative PCR and Western blotting were utilized to investigate the expression of transcription factors FOXO1, FOXL2, and NR5A2 in the ovary at the mRNA and protein levels, respectively, and their relationships with follicle numbers were analyzed, to reveal the potential molecular pathways through which photoperiod regulates follicle development in the striped hamster. Results The results demonstrate that LP enhances the synthesis of FSH, promotes granulosa cell proliferation, and stimulates follicle development, whereas SP exerts an opposing effect in the striped hamster. FSH is a key hormone involved in follicle development regulated by photoperiods, and CCND2 influences follicle development by modulating granulosa cell proliferation. Additionally, photoperiod alters the expression levels of transcription factors FOXO1, FOXL2, and NR5A2. Correlation analyses revealed that serum FSH concentration was significantly positively correlated with the expression levels of FOXO1 and FOXL2. In turn, the expression of FOXO1 and FOXL2 was significantly positively associated with that of NR5A2, which also showed a significant positive correlation with CCND2 expression. These results suggest a potential regulatory pathway—FSH-FOX-NR5A2-CCND2—involved in photoperiod-dependent follicle development in the striped hamster. Conclusion The FSH-FOX-NR5A2-CCND2 pathway represents a potential molecular mechanism by which photoperiod regulates follicle development, supported by robust correlative evidence in the striped hamster. The transcription factors FOXO1, FOXL2, and NR5A2 are identified as candidate targets of reproductive activity, with NR5A2 showing a stronger correlation than FOXO1 and FOXL2, thus providing a theoretical foundation for the rational control of rodent population dynamics.